DYNAMICS OF SOIL CHEMICAL PROPERTIES UNDER Illicium verum Hook FORESTS IN VAN QUAN, LANG SON - Thi Bich Phuong, Nguyen; Manh Hung, Bui (Journal of Forestry Science and Technology, 2021)
Dynamics in soil chemical properties are greatly influenced by vegetation. The study was conducted under Illicium verum plantations 21 years and 31 years in Van Quan, Lang Son. At each age level of the forest, soil samples were collected at different depths: 0 – 10 cm, 10 – 20 cm and 20 – 50 cm layers. The results showed that there were significant differences in hydrolytic acidity and humus content between the two forest ages and between the soil depths. The amount of soil organic carbon (SOC) differed significantly between 21-year-old forest (19.83 tons/ha in average) and 31-year-old forest (30.13 tons/ha in average) and tended to decrease with soil depths. The content of bio-available nitrogen in soils was poor (reached 0.55 – 1.71 mg/100g dried soil at 21-year-old forest and 1.37 – 1.75 mg/100g dried soil at 31-year-old forest). There was no difference between the two forest age classes and soil depths. Similarly, the content of bio-available phosphorus at the two forest age levels did not differ (all from 0.13 to 0.17 mg/100g dried soil) and tended to decrease gradually with soil depths. The bio-available content potassium was all poor and also did not differ significantly between between 21-year-old forest (3.85 - 4.31 mg/100g dried soil) and 31-year-old forest (3.88 - 4.74 mg/100g dried soil). There was no difference in the potassium content between soil depths in the 21-year-old forest, but there was a statistical difference between the soil depths in the 31-year-old forest. A pathway equation indicated that humus content had a proportional relationship with the soil chemical properties except for the available potassium at both Illicium verum forest age levels.